Menelaah Peran Pendidikan Kewirausahaan dalam Mendorong Niat Mahasiswa untuk Bertransisi dari Kampus ke Dunia Bisnis - Nia Daniati; Yayah Sopianah; Melkisedek O. Nubatonis; Deni Hermana; Muhammad Fiqih Sabilillah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
Although entrepreneurship education is essential in driving economic growth, there are still challenges in fostering entrepreneurial intentions among students. One of the main obstacles is the lack of understanding of how elements within the Entrepreneurship Education Ecosystem (EEE) influence entrepreneurial intentions. Research Objective is to explain the effect of attitude, subjective norm, and entrepreneurial self-efficacy on entrepreneurial behavior, mediated by entrepreneurial intentions and moderated by the Entrepreneurship Education Ecosystem (EEE). A quantitative survey was conducted with 286 students from Poltekkes in Indonesia, with data analysis using Structural Equation Modeling (SEM) co variant. The results show a positive relationship between access to entrepreneurship support systems and increased entrepreneurial intentions among students, as well as the importance of EEE elements in shaping entrepreneurial attitude and self-efficacy. These findings provide guidance for higher education institutions and policymakers to strengthen entrepreneurship support systems to enhance students' entrepreneurial intentions. The study also expands understanding of the role of EEE in fostering stronger entrepreneurial intentions.